C‐phycocyanin as a highly attractive model system in protein crystallography: unique crystallization properties and packing‐diversity screening. Issue 2 (8th February 2021) - Sarrou, Iosifina; Feiler, Christian G.; Falke, Sven; Peard, Nolan; Yefanov, Oleksandr; Chapman, Henry
Abstract : C‐phycocyanin, a photosynthetic antenna protein from the cyanobacterium Thermosynechococcus elongatus, was crystallized in hundreds of different conditions, producing protein crystals with various sizes and morphologies. Among the many diffraction data sets that were collected, high‐resolution X‐ray structures with novel symmetries were solved and are discussed with the aim of providing a highly adaptable experimental model system. Abstract : The unique crystallization properties of the antenna protein C‐phycocyanin (C‐PC) from the thermophilic cyanobacterium Thermosynechococcus elongatus are reported and discussed. C‐PC crystallizes in hundreds of significantly different conditions within a broad pH range and in the presence of a wide variety of precipitants and additives. Remarkably, the crystal dimensions vary from a few micrometres, as used in serial crystallography, to several hundred micrometres, with a very diverse crystal morphology. More than 100 unique single‐crystal X‐ray diffraction data sets were collected from randomly selected crystals and analysed. The addition of small‐molecule additives revealed three new crystal packings of C‐PC, which are discussed in detail. The high propensity of this protein to crystallize, combined with its natural blue colour and its fluorescence characteristics, make it an excellent candidate as a superior and highly adaptable model system in crystallography. C‐PC can be used in technical and methods development approaches for X‐ray and neutron diffraction techniques, and as a system for comprehending the fundamental principles of protein crystallography.